Temporal trends in dementias in older adults attributable to high fasting plasma glucose from 1990 to 2021 and forecasted disease burden in 2040 in China and globally - Dai, Pinyuan; Yu, Jie; Lin, Yongxing; Zhou, Xiaoyan; Wang, Hao; Gong, Weiwei; Pan, Jin; Guan, Yunqi; Zhong, Jieming; Li, Na; Liu, Zuyun (Frontiers in Public Health, 2025)
IntroductionThe Global Burden of Diseases Study systematically updates the dementia burden attributable to high fasting plasma glucose (HFPG) to investigate the temporal trends of dementia burden and promote comparisons between countries, sexes, and age groups. In this study, we aimed to estimate the disease burden of dementia attributable to HFPG using an age-period-cohort model in adults aged >60 years from 1990 to 2021 and forecast the mortality and disability-adjusted life-years (DALYs) rates in China and globally in 2040.MethodData on the mortality and DALYs rates of dementia attributable to HFPG in China and globally were extracted from the Global Burden of Disease Study 2021. An age-period-cohort model was used to estimate the net drift, local drift, fitted longitudinal age-specific rates, and period/cohort relative risks from 1990 to 2021. The Bayesian age-period-cohort model was used to predict future mortality and DALYs rates from 2022 to 2040.ResultsThe net drifts showed an overall upward trend in the dementia burden attributable to HFPG in China and globally from 1990 to 2021, with a much slower trend in China. A constantly rising risk for age and birth cohort effects was observed, while period effects presented a globally constantly increasing risk and two inflection points in China, probably due to healthcare reform. The forecasted disease burden by 2040 demonstrated an increasing trend globally and a declining trend in China.ConclusionThe burden of dementia attributable to HFPG has consistently increased globally over the past 30 years but has gradually declined in China in recent years. China’s strategies for preventing and managing diabetes and dementia may provide valuable insights for other regions. Further targeted policies are required to reduce the burden on females and older adults, particularly to improve their quality of life.